Perceived stress and Coping Strategies During COVID-19 among Nursing and Arts / Science students- A Comparative study - Moly, K. T; Lakshmi, Aparna C.; Vijayan, Sony; Vadakkepatt, Anisha (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Background: The COVID-19 pandemic has posed a significant challenge to education systems worldwide, adversely affecting student life. This study aimed to compare perceived stress and coping strategies among Nursing and Arts/Science students during the pandemic. Methods: This quantitative analytical study used the Cochran formula to determine sample size. A stratified sampling technique selected 93 Nursing students and 198 Arts/Science students. Perceived stress was measured using Sheldon Cohen’s Perceived Stress Scale and coping strategies with Brief COPE Strategies, alongside a self-developed sociodemographic questionnaire and a five-point scale for stressors. Results: Most subjects in both groups were aged 17-20 years (55% Nursing vs. 73% Arts/Science) and female (99% Nursing vs. 91% Arts/Science). Key stressors included COVID-19 restrictions (72.1% Nursing vs. 77.8% Arts/Science), with the highest stress from being unable to leave home and financial issues. Moderate perceived stress was common in both groups (64.5% Nursing vs. 79.3% Arts/Science), while high perceived stress was more prevalent among Nursing students (19.4% vs. 9.6%). A majority of Nursing students had high coping scores (57%) compared to Arts/Science students (2%), who predominantly had moderate coping scores (79.3% vs. 38% Nursing). Maladaptive coping strategies were prevalent in both groups, with mean scores of 26.09 (SD 6.569) for Nursing and 23.53 (SD 4.537) for Arts/Science. There was a significant difference in coping strategies between the groups (t=10.22, p<0.01), but no significant association between perceived stress and sociodemographic data. Conclusion: The use of maladaptive coping strategies during COVID-19 among students may adversely affect their long-term attitudes and health. Strengthening counseling services and educating on adaptive coping methods are essential for student well-being.